Guardians perception of the normative need for dental care of pediatric patients - Glória Fernanda Barbosa Araújo Castro; Erika Calvano Kuchler; Maria Bárbara Carvalho Torres Guimarães; Lucianne Cople Maia de Faria (Faculdade São Leopoldo Mandic, 2009)
Objective:To identify the guardians' perception of the need for dental treatment of pediatric patients, as well as the normative needs for the treatment of children. Methods: The medical charts of 355 pediatric patients between the ages of zero and 12 years, attended at the Higher Education Institute, were selected, and from these, data were collected from the guardians with reference to their age and educational level. The normative need for treatment of the children were clinically assessed, as well as the perception of the guardians with regard to these needs. The data were tabulated by the Chi-square test. Results: The guardians' mean age was 35.5 + 8 years, 84% of them being the mothers themselves, the majority of whom had incomplete primary schooling (36%). The normative need for treatment most noted in the children was (dentisteria) dental care(?) in posterior teeth (52%). The majority of the guardians (41%) were late in identifying the restorative needs, or underestimated some of the need for treatment (35%). Only 3% of the sample identified the need for early treatment. No relationship was observed between the guardians' perception and educational level (χ2-p>0.05). However, the guardians under the age of 35, perceived the needs better, although late (χ2-p<0.05). Conclusion: It was concluded that although the guardians' perception was influenced by age, it was inadequate because they underestimated the normative needs for dental treatment of the children.